2009
DOI: 10.1128/aem.01914-08
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Mycobacterium abscessus Defined Glycopeptidolipid Mutants: Comparison of Genetic Tools

Abstract: Mycobacterium abscessus is a rapidly growing mycobacterial species that can be involved in pulmonary and disseminated infections in immunosuppressed or young cystic fibrosis patients. It is an emerging pathogen and has attracted recent attention due to the numerous cases of infection; furthermore, genomic tools have been developed for this species. Nevertheless, the study of this species has until now been limited to spontaneous variants. We report here a comparison of three different mutagenesis systems-the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
95
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(103 citation statements)
references
References 42 publications
(58 reference statements)
6
95
1
Order By: Relevance
“…We have provided evidence that expression of GPL facilitates the M. abscessus colonization phenotype, but 'masks' underlying bioactive cell-wall lipids involved in virulence (Rhoades et al, 2009). In this study we have used genetic recombineering to delete the M. abscessus 390S mmpL4b gene, a gene coding for a membrane protein which has been found to play an essential role in GPL expression by NTM (Recht et al, 2000;Ripoll et al, 2007;Medjahed & Reyrat, 2009). Using this deletion mutant we provide direct evidence that GPL plays a role in both the colonization and invasion phenotypes of M. abscessus.…”
Section: Introductionmentioning
confidence: 99%
“…We have provided evidence that expression of GPL facilitates the M. abscessus colonization phenotype, but 'masks' underlying bioactive cell-wall lipids involved in virulence (Rhoades et al, 2009). In this study we have used genetic recombineering to delete the M. abscessus 390S mmpL4b gene, a gene coding for a membrane protein which has been found to play an essential role in GPL expression by NTM (Recht et al, 2000;Ripoll et al, 2007;Medjahed & Reyrat, 2009). Using this deletion mutant we provide direct evidence that GPL plays a role in both the colonization and invasion phenotypes of M. abscessus.…”
Section: Introductionmentioning
confidence: 99%
“…The key to this is a suitable counterselectable marker, such as sacB (conferring sucrose sensitivity), rpsL (conferring streptomycin susceptibility in a streptomycin-resistant background) or galK (conferring 2-deoxygalactose susceptibility) [14,[27][28][29]. Others have shown that sacB does not work in M. abscessus, and the rpsL system requires a pre-existing streptomycin resistance mutation in the choromosomal copy of rpsL, which complicates strain construction [16,23,29]. Additionally, in preliminary experiments (not shown), we found it difficult to isolate streptomycin-resistant mutants that could be used with our previously developed rpsL suicide vectors.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, M. abscessus is refractory to allelic exchange using the TM4 mycobacteriophage-based specialized transduction system [16]. Electroporation of dsDNA can work, either without [17] or with the expression of recombineering proteins [16,18], but the efficiency is low [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations